Art lab for kids 52 creative adventures in drawing, painting, printmaking, paper, and mixed media-for budding artists of all ages - Schwake, Susan; Schwake, Rainer (Beverly, MA : Quarry Books, 2012)
Each lesson features and relates to the work and style of a contemporary artist and their unique style. The labs can be used as singular projects or to build up to a year of hands-on fine art experiences. Grouped by medium, the labs are set up loosely to build skills upon the previous ones; however, you can begin anywhere.
Includes index.
4 - 10 years
Keywords: Art -- Technique